(untitled) (Third Sector Social Economic Review, 2015)
Cooperatives taking place between the states and the individuals bringing their powers together for increasing their benefits in order to succeed in doing the activities which cannot be carried out on their own, have emerged as social solidarity organizations. Cooperatives standing an intermediate structure between the states and individuals getting together to increase their benefits, also being established as voluntary organizations, can, in modern and popular terms, be examined as nongovernmental organizations (NGOs). This study drawing a map of cooperatives, intends to establish their social resources, by discovering the numbers of their members, branches, sort of activities and so on, in a sense aiming to reveal characteristics of cooperatives. Cooperatives are related to both locally and in general to the direct development, sustainable development. Group solidarity of the individuals targeting the economic development by getting together mobilizing this consciousness and theunity of their powers emerging in this way, show how to built a power block with solidarity spirit of single individuals. Cooperatives providing indirect contribution to the development of a democratic consciousness, lead up concurrently to the emergence of the country’s democratic and participatory political culture. Hence cooperatives can be considered as direct cradle of democracies due to the decisions taken by their own members relating to the decisions of their own issues.